DIPLOMACY IN THE CONTEXT OF THE MODERN HYBRID WAR - Набока, А. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
А concept «diplomacy» and role of diplomacy in the context of modern hybrid war are analyzed. Features and methods of political struggle, particularities and methods of diplomacy in contemporary political realities also are examined. The special attention is spared the reconstruction of international relations and forming a new world order. The notions of «hybrid war», «diplomatic pressure», «international cooperation» are singled out. The essence and methods of diplomacy as arts in different historical epochs are analyzed.